OP0124 The Protective Effect of HLA-DRB1*13 Alleles During Specific Phases in the Development of ACPA-Positive RA. (9th June 2015) - van Heemst, J.; Hensvold, A.H.; Jiang, X.; van Steenbergen, H.; Lundberg, K.; Klareskog, L.; Huizinga, T.W.; van der Helm-van Mil, A.H.; Catrina, A.I.; Toes, R.E.; van der Woude, D.
Abstract : Background: HLA-DRB1 shared epitope (SE) alleles predispose to anti-citrullinated protein antibody (ACPA-)positive rheumatoid arthritis (RA), whereas HLA-DRB1*13 alleles exert an independent protective effect. It is however unknown at which phase of disease development (seroconversion, ACPA maturation, disease onset, disease outcome) these alleles exert their effect. Objectives: To better understand the HLA-DRB1*13-mediated protective effect, we examined the association between HLA-DRB1*13 and the presence of ACPA (: systemic autoimmunity associated with RA) in healthy and RA individuals. Furthermore, we investigated the association between HLA-DRB1*13 and ACPA characteristics, as well as clinical outcome measures. Methods: The association between HLA-DRB1*13 alleles and the presence of ACPA(-positive systemic autoimmunity associated with RA), or ACPA-positive RA was assessed in 10748 individuals from a population setting (the Swedish twin registry). The association of HLA-DRB1*13 with ACPA levels and antibody fine-specificities was studied in ACPA-positive RA patients from two independent cohorts, the Swedish Epidemiological Investigation of Rheumatoid Arthritis (EIRA, n=1224) and the Dutch Leiden Early Arthritis Clinic (EAC, n=441). Disease activity at inclusion and disease outcome in the form of DMARD-free sustained remission and radiographic progression was assessed in more than 600 RA patients from the EAC. Results: HLA-DRB1*13 alleles are present in 16% of ACPA-positive RA patients, 22% of individuals with ACPA(-positive systemic autoimmunity associated with RA) and 28% of ACPA-negative individuals. Thus HLA-DRB1*13 is associated with protection from ACPA-positive RA, but not with significant protection (p-value 0.09) from ACPA(-positive systemic autoimmunity associated with RA). In established ACPA-positive RA, HLA-DRB1*13 is associated with lower ACPA-levels (EIRA: 447 U/ml versus 691 U/ml, p-value: 0, 0002) and decreased recognition of the ACPA fine-specificities citrullinated vimentin and/or alpha-enolase (EIRA: 57% versus 76% of patients positive for these fine specificities, p<0.0001). HLA-DRB1*13 is not associated with markers of disease activity at presentation or with the clinical outcome measures radiographic progression or sustained DMARD-free remission. Conclusions: The present data suggest that the protective HLA-DRB1*13 alleles mainly exert their effect in the timeframe between the development of ACPA(-positive systemic autoimmunity) and the onset of ACPA-positive disease. The HLA-DRB1*13 alleles can influence ACPA characteristics, but do not appear to affect the disease course after seroconversion, similar to the predisposing SE alleles. This implies that therapeutic strategies aimed at emulating the effect of the protective HLA-DBR1*13 alleles may be most effective in ACPA-positive healthy individuals who are at risk for developing RA. Disclosure of Interest: None declared